A autoridade dos direitos humanos entre autonomia e bens básicos: o debate filosófico da teoria da lei natural de John Finnis com o positivismo liberal de Joseph Raz - PINHEIRO, Victor Sales (Escola da Magistratura do Rio Grande do Norte, 2024)
This research explores the normative concept of human rights by summarizing the debate between the natural law theory of John Finnis and the liberal positivism of Joseph Raz, two of the most relevant analytical theorists of contemporary jurisprudence. To follow this debate, the article presents and criticizes three central arguments of Raz for the understanding of human rights: his thesis of unlimited authority, considered as exclusionary reason; his conception of practical reason and the autonomy of subjective interests; and the emergent order of human rights as limiting sovereignty. Then, the paper addresses Finnis' theory of natural law, also in three core arguments for the elucidation of human rights concept: the thesis of basic human goods as the foundation of natural rights; the universality and intrinsic value of human rights, according to the dignity of the human person; and the relationship between legitimate authority and the common good, based on the normativity of human rights. Finally, it concludes that Finnis is able to respond to the difficulties identified in Raz. Its methodology is hypothetical-deductive, based on bibliographical research, following a review of the primary and secondary literature of these authors and formulating general hypotheses about human rights.